Shakespeare's early history plays from chronicle to stage - Goy-Blanquet, Dominique (Oxford University Press, 2009)
Like many of his fellow playwrights, Shakespeare turned to national history for inspiration. This study provides a comparison of the 'Henry VI' plays and 'Richard III' with their sources, demonstrating how the ideological and technical problems of turning history into drama were solved.